ANALYSIS OF CASH FLOW CAPABILITY AND PROFITS FOR BANKING SUSTAINABILITY - Nuryani, Ni Nyoman Juli; Gorda, A. A. N. Oka Suryadinatha; Trisnawati, Ni Luh De Erik; Septiari, Ketut Fransiska; Wandira, Ketut Ayu (International Journal of Application on Economics and Business, 2023)
Financial reports play a crucial role in enhancing cash flow and profits. The focus of the issue in this study is related to cash flow and profits. The objective of this research is to assess the impact of the analysis of cash flow and profit capabilities in the banking context, by conducting a study at PT. Bank BPD Bali Singaraja Branch. This research employs various analytical techniques, including validity and reliability tests, multiple linear regression analysis, classic assumption tests, multiple correlation analyses, determination analyses, T-Test, and F-Test, with the aim of predicting cash flow. The research findings indicate that both cash flow and profits have a significant influence on future cash flow at PT. BPD Bali Singaraja Branch. These results are reinforced by hypothesis testing using the T-Test, where each t-value > t-table (3.007 > 1.667) for cash flow and (2.079 > 1.667) for profits, confirming the acceptance of both hypotheses. Partial correlation values show a moderate relationship (0.453) between cash flow (X1) and the dependent variable (Y), as well as a strong relationship (0.360) between profits (X2) and the dependent variable (Y). The impact of independent variables on dependent variables is indicated by a determination value of 27.5% and a correlation value of 0.525, demonstrating a low positive correlation between the two. The conclusion drawn from this research is that both cash flow and profits positively influence future cash flow at PT. Bank BPD Bali Singaraja Branch. The F-Test indicates that the F-value > F-table (8.543 > 3.19), indicating that cash flow and profits together have an impact on future cash flow in the bank.